2021
DOI: 10.1108/crr-06-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing organisational resilience through knowledge management: a qualitative inquiry of parastatals

Abstract: PurposeThis paper makes a qualitative inquiry about how organisational resilience can be nurtured through knowledge management practices in parastatals to cope with environmental challenges. The paper identifies parastatal challenges and organisational resilience mechanisms.Design/methodology/approachA phenomenological paradigm through conversational discourse is used to investigate the building of organisational resilience. Twelve cases are covered to provide data that is interpretively analysed using direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Interpretivism enables the researcher to obtain understanding about the phenomenon through interactions with participants (Manroop, 2017). This is in line with Mafabi and Kabagambe’s (2021) assertion that “reality is in the minds of the people”, hence the need to tap into their perceptions. The authors then used a qualitative methodology through in-depth interviews to obtain knowledge about relational people management.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…Interpretivism enables the researcher to obtain understanding about the phenomenon through interactions with participants (Manroop, 2017). This is in line with Mafabi and Kabagambe’s (2021) assertion that “reality is in the minds of the people”, hence the need to tap into their perceptions. The authors then used a qualitative methodology through in-depth interviews to obtain knowledge about relational people management.…”
Section: Methodssupporting
confidence: 80%
“…According to Smith (2012), context gives the prevailing situation that needed to be changed, actions comprise of the activities to overcome the challenges, results consist of the outcomes and lessons are the learning points drawn from the story. As indicated by Mafabi and Kabagambe (2021), these respective themes became the unit of analysis. The initial coding was done by the lead researcher which was later confirmed by the entire research team during several meetings.…”
Section: Discussionmentioning
confidence: 99%
“…According to Smith (2012), context gives the prevailing challenges, actions entail what was done to overcome the challenges, results consist of the outcomes and lessons are the learning points drawn from the story. These themes became the unit of analysis (Mafabi and Kabagambe, 2021). The initial coding was done by the main author and later confirmed by the rest of the authors to eliminate bias from the coding process (Strauss and Corbin, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…KM helps to nurture organizational resilience in many ways in the information resilience society. Many studies have found that there is a significant relationship between KM and organizational resilience e.g., KM and organizational resilience (Mafabi, Munene & Ntayi, 2012), nurturing organizational resilience through KM (Mafabi & Kabagambe, 2021). Effective KM (systematic acquisition, creation, sharing, storing, and use of knowledge) leads to innovation, success and competitiveness (Nonaka & Takeuchi, 1995; Darroch, 2005).…”
Section: Knowledge Management Strategies In An Information‐resilient ...mentioning
confidence: 99%